INVESTIGATION OF THE NUCLEAR REACTIONS RELEVANT FOR THERMONUCLEAR FUSION - Kabatayeva, R.S. (Recent Contributions to Physics, 2017)
Exothermal nuclear reactions of interaction of particles with 6Li and 7Li nuclei are considered. It is shown that resonant mechanism of interaction is mainly connected with the dominant cluster structure of these nuclei. The main channels of light nuclei interaction are shown, their peculiarities are discussed, and reactions energies are given